Boosting biohydrogen production from dairy wastewater via sludge immobilized beads incorporated with polyaniline nanoparticles. (July 2022) - Hellal, Mohamed S.; Abou-Taleb, Enas M.; Rashad, Ahmed M.; Hassan, Gamal K.
Abstract: In this study, the immobilization of anaerobic sludge in sodium alginate (SA) with polyaniline (PANI) nanoparticles (NPs) was performed for producing biohydrogen from dairy wastewater (DWW). The effect of PANI on immobilization in SA was investigated at different PANI concentrations (5, 10, 20, 40, and 80 mg L −1 ). DWW, PANI NPs, and immobilized beads were characterized through physicochemical analysis, surface area, X-ray diffractometry, and scanning electron microscopy (SEM). The results revealed that the immobilization of anaerobic sludge in SA with PANI NPs enhanced the degradation of organic matter in DWW into volatile fatty acids and biohydrogen yield. There is a direct relationship between PANI NPs concentration in SA, degradation in DWW, and bio-hydrogen production. The degradation of organic matter in terms of chemical oxygen demand reached 75.5% at the optimum dose of PANI NPs (40 mg L −1 ), which confirmed the high reactivity of PANI NPs with SA compared with the control sample. In addition, at 40 mg L −1 PANI NPs concentration, the maximum hydrogen yield were 54.5 mL g −1  VS from anaerobic fermentation was obtained with a 285% increase compared with the fermentation without using any PANI. The SEM image of beads before and after treatment indicated that the addition of PANI NPs up to 40 mg L −1 enhanced the production of bio-hydrogen yield through SA in a regular pattern, whereas increasing the concentration to 80 mg L −1 resulted in shrinking of SA surface and consequently decreased the biohydrogen yield. Highlights: Anaerobic immobilization was utilized to enhance biohydrogen production. Sodium alginate beads acted as a core shell for granular anaerobic sludge. Treatment and energy production from dairy wastewater has been achieved. Polyaniline nanoparticle improved the sodium alginate surface distribution.